The Relationship between Perceived Benefit and Perceived Risk Toward Electric Vehicle (EV) Purchase Intention Among Consumers in Kuala Lumpur, Malaysia. - Kevin Phua Chin An,; Nor Kamariah Kamaruddin, (Research in Management of Technology and Business, 2024)
Fossil fuel reliance in energy production worsens climate change due to greenhouse gas emissions. The increased number of conventional vehicle owners leads to higher energy consumption, exacerbating greenhouse gas production and posing energy security and environmental concerns. Electric vehicles (EVs) offer a promising solution to reduce this dependency and combat environmental challenges. Conducting a thorough study is crucial to grasping the factors affecting the purchasing intentions of conventional vehicle users, ensuring the sustainability of electric vehicle (EV) users, and improving EV purchase strategies. The study's objective is to clarify the level of perceived benefit, perceived risk, and electric vehicle (EV) purchase intention, as well as identify the relationship between perceived benefit and perceived risk toward Electric Vehicle (EV) purchase intention among consumers in Kuala Lumpur. The respondents in this study were 399 vehicle license holders in Kuala Lumpur, Malaysia. The response rate was 78.20% and data was collected and analysed using the Statistical Package for Social Science (SPSS). This research used a quantitative approach and an online survey was conducted by using a questionnaire as the research instrument. The Descriptive analysis and Spearman analysis were employed. It signifies a moderate level of perceived benefit and a high level of perceived risk, thus supporting all the hypotheses. Moreover, the findings report findings for this study are likely to reveal a positive relationship between perceived benefits and perceived risks towards electric vehicle (EV) purchase intention. Furthermore, this research can heighten awareness among environmentally conscious individuals, prompting an evaluation and potential adjustment of their transportation preferences. The Malaysian government offers incentives, such as import duty, excise duty, and sales tax exemptions, to encourage electric vehicle (EV) ownership and promote green sustainability.